2012
DOI: 10.1103/physrevb.86.205130
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic metamaterial as super absorber for scattered fields generated at its surface

Abstract: We show that hyperbolic metamaterials (HMs) that exhibit hyperbolic wave-vector dispersion diagrams possess two important features related to super absorption: The total power scattered by a nanosphere is (i) greatly enhanced when placed at the HM surface, compared to other material surfaces, and (ii) almost totally directed into the HM. We show that these two features are peculiar of HM interfaces, and we support them using a spectral theory study of transverse-electric and magnetic waves scattered by a subwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 20 publications
5
112
0
Order By: Relevance
“…When the period is increased both tot free space / P P and down up / P P are enhanced. This is in good agreement with the results in [1] drawn for a single dipole. Moreover a sharp peak appears for 300 nm a b = = case, which is attributed to the coupling to a surface mode.…”
Section: Illustrative Examplessupporting
confidence: 82%
See 3 more Smart Citations
“…When the period is increased both tot free space / P P and down up / P P are enhanced. This is in good agreement with the results in [1] drawn for a single dipole. Moreover a sharp peak appears for 300 nm a b = = case, which is attributed to the coupling to a surface mode.…”
Section: Illustrative Examplessupporting
confidence: 82%
“…For example, when h is increased from 5 to 25 nm as reported in Fig. 3, the two ratios above degrade significantly, confirming the importance of evanescent coupling of the field from the dipoles to the HM, in agreement with the results drawn in [1] for a single dipole. VI.…”
Section: Illustrative Examplessupporting
confidence: 78%
See 2 more Smart Citations
“…HMMs can be designed for use in efficient and innovative absorbers to enhance the decay rate of emitters near the surface. 12 Tumkur 13 showed that metallic and lamellar metal-dielectric HMM substrates can tune and enhance the absorption of thin dye-doped polymeric films.…”
Section: Introductionmentioning
confidence: 99%